Does Eco-label Format Influence Consumers’ Valuation of Fruit-Producing Plants? - Hayk Khachatryan; Alicia Rihn; Xuan Wei (EDIS, 2020)
Consumer demand for environmentally friendly products has increased, and consumers are willing to pay more for environmentally friendly fruit-producing plants. With the increased demand, however, the number and variety of eco-labels describing the environmentally friendly qualities of plants has also increased, which could confuse consumers and decrease label effectiveness. Previous studies found that well-designed eco-labels improve consumer understanding, clarity, and choice. This 6-page fact sheet written by Hayk Khachatryan, Alicia Rihn, and Xuan Wei and published by the UF/IFAS Food and Resource Economics Department summarizes a study that addressed how different eco-label formats (text vs. logo) impact consumer visual attention, preferences, and valuations of fruit-producing plants. https://edis.ifas.ufl.edu/fe1074